Evolutionary Dynamics of 5S rDNA and Recurrent Association of Transposable Elements in Electric Fish of the Family Gymnotidae (Gymnotiformes): The Case of Gymnotus mamiraua - Silva, M. R. da; Barbosa, Patrícia; Artoni, Roberto Ferreira; Feldberg, Eliana (Cytogenetic and Genome Research, 2016)
Gymnotidae is a family of electric fish endemic to the Neotropics consisting of 2 genera: Electrophorus and Gymnotus. The genus Gymnotus is widely distributed and is found in all of the major Brazilian river systems. Physical and molecular mapping data for the ribosomal DNA (rDNA) in this genus are still scarce, with its chromosomal location known in only 11 species. As other species of Gymnotus with 2n = 54 chromosomes from the Paraná-Paraguay basin, G. mamiraua was found to have a large number of 5S rDNA sites. Isolation and cloning of the 5S rDNA sequences from G. mamiraua identified a fragment of a transposable element similar to the Tc1/mariner transposon associated with a non-transcribed spacer. Double fluorescence in situ hybridization analysis of this element and the 5S rDNA showed that they were colocalized on several chromosomes, in addition to acting as nonsyntenic markers on others. Our data show the association between these sequences and suggest that the Tc1 retrotransposon may be the agent that drives the spread of these 5S rDNA-like sequences in the G. mamiraua genome. © 2016 S. Karger AG, Basel.
Keywords: Dna 5s; Retroposon; Ribosome Dna; Rna 5s; Chromosomal Mapping; Dna Isolation; Dna Sequence; Dna Synthesis; Fish Genetics; In Situ Hybridization, Fluorescence; Gymnotiformes; Gymnotus Mamiraua; Cloning, Molecular; Evolution, Molecular; Nonhuman; Priority Journal; Retroposon; Sequence Analysis; Transposon; Animals; Female; Genetics; Genome; Gymnotiformes; Male; Animal; Chromosome Mapping; Ribosomal Dna; Evolution, Molecular; Female; Genome; Gymnotiformes; In Situ Hybridization, Fluorescence; Male; Retroelements; Rna, Ribosomal, 5s